Rationing Limited Healthcare Resources in the COVID‐19 Era and Beyond: Ethical Considerations Regarding Older Adults. Issue 6 (14th June 2020) - Farrell, Timothy W.; Francis, Leslie; Brown, Teneille; Ferrante, Lauren E.; Widera, Eric; Rhodes, Ramona; Rosen, Tony; Hwang, Ula; Witt, Leah J.; Thothala, Niranjan; Liu, Shan W.; Vitale, Caroline A.; et al.
Abstract : Coronavirus disease 2019 (COVID‐19) continues to impact older adults disproportionately with respect to serious consequences ranging from severe illness and hospitalization to increased mortality risk. Concurrently, concerns about potential shortages of healthcare professionals and health supplies to address these issues have focused attention on how these resources are ultimately allocated and used. Some strategies, for example, misguidedly use age as an arbitrary criterion that disfavors older adults in resource allocation decisions. This is a companion article to the American Geriatrics Society (AGS) position statement, "Resource Allocation Strategies and Age‐Related Considerations in the COVID‐19 Era and Beyond." It is intended to inform stakeholders including hospitals, health systems, and policymakers about ethical considerations that should be considered when developing strategies for allocation of scarce resources during an emergency involving older adults. This review presents the legal and ethical background for the position statement and discusses these issues that informed the development of the AGS positions: (1) age as a determining factor, (2) age as a tiebreaker, (3) criteria with a differential impact on older adults, (4) individual choices and advance directives, (5) racial/ethnic disparities and resource allocation, and (6) scoring systems and their impact on older adults. It also considers the role of advance directives as expressions of individual preferences in pandemics. J Am Geriatr Soc 68:1143–1149, 2020. Abstract : See related paper by Farrell et al .